Mineral profile of feeds, fodders and biochemical profile of animals in west- central table land zone of Odisha - SINGH, R K; MISHRA, S K; SWAIN, R K; DEHURI, P K; SAHOO, G (The Indian Journal of Animal Sciences, 2011)
Sample of feeds and fodders and serum samples of cows in 8 villages, 2 from each block and 2 blocks from each of the 2 districts namely Bargarh and Jharsuguda of West-central table land zone (WCTLZ) of Odisha were collected and analysed for macro and micro mineral content. Among the fodders, paddy straw was deficient in calcium (Ca), phosphorus (P), copper (Cu) and manganese (Mn). Deficiency of P was observed in most of the fodders. Most of the concentrate contained higher level of the analysed minerals. The average serum Ca, P, zinc (Zn), Cu, Mn and iron (Fe) content of cows in WCTLZ were found to be 6.81±0.14 mg/dl, 3.67±0.09 mg/dl, 0.90±0.02 pmm, 0.68±0.01 pmm, 0.26±0.004 pmm and 2.38±0.07 pmm, respectively. The percentage of animals deficient in serum Ca, P, Zn, Cu and Mn were observed to be 75.8, 72.5, 13.3, 29.1, 9.1 and 5.8 %, respectively. The serum mineral content of the animals of WCTLZ was highly deficient in Ca and P. Deficiency of Zn, Cu, Mn and Fe was also noticed in some animals. The serum glucose, cholesterol, protein, albumin and globulin content of the animals in WCTLZ were 45.87±1.56 mg/dl, 63.99±2.84 mg/dl, 4.49±0.09g/dl, 2.16±0.05g/dl and 2.32±0.08g/dl, respectively. Based on the study, supplementation of deficient minerals, viz. Ca, P, Zn and Cu and protein and energy in the diet of cattle under existing feeding practices in WCTLZ of Odisha is imperative for better health and productivity.